2000
DOI: 10.1016/s0886-3350(00)00583-6
|View full text |Cite
|
Sign up to set email alerts
|

Posterior capsule opacification 3 years after implantation of an AcrySof and a MemoryLens in fellow eyes

Abstract: The 3 year clinical data of fellow eyes indicate that the AcrySof IOL causes less PCO than the MemoryLens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
6

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 19 publications
0
12
0
6
Order By: Relevance
“…[1][2][3][4] Furthermore, most studies that compared the occurrence of PCO between IOLs, including ours, [5][6][7] showed that it is least in those eyes with an AcrySof IOL. [14][15][16][17][18][19][20][21] However, until now there has been no study comparing the degree of PCO between fellow eyes with AcrySof and Sensar IOLs. In a recent study, we found that the degree of PCO is very slight in eyes with the Sensar IOL that has a sharp posterior edge.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Furthermore, most studies that compared the occurrence of PCO between IOLs, including ours, [5][6][7] showed that it is least in those eyes with an AcrySof IOL. [14][15][16][17][18][19][20][21] However, until now there has been no study comparing the degree of PCO between fellow eyes with AcrySof and Sensar IOLs. In a recent study, we found that the degree of PCO is very slight in eyes with the Sensar IOL that has a sharp posterior edge.…”
Section: Discussionmentioning
confidence: 99%
“…Viele Studien haben gezeigt, dass die höchste PCO bei Patienten mit implantierten PMMA-Linsen zu finden ist und die niedrigste bei jenen mit Akryllinsen [4,5,27].…”
Section: Erörterungunclassified
“…Deshalb wurden in allen Fällen Akryl-IOL implantiert. Es ist bekannt, dass Akryl-IOL eine signifikant niedrigere PCO-Häufigkeit als andere Linsen haben [4,27]. Die PCO-Inzidenz war 7-11% nach einem Jahr und 10-20% nach 3 Jahren [4,27].…”
Section: Erörterungunclassified
See 2 more Smart Citations